2017
DOI: 10.3791/55757
|View full text |Cite
|
Sign up to set email alerts
|

<em>In Vitro</em> Differentiation of Human Mesenchymal Stem Cells into Functional Cardiomyocyte-like Cells

Abstract: Myocardial infarction and the subsequent ischemic cascade result in the extensive loss of cardiomyocytes, leading to congestive heart failure, the leading cause of mortality worldwide. Mesenchymal stem cells (MSCs) are a promising option for cell-based therapies to replace current, invasive techniques. MSCs can differentiate into mesenchymal lineages, including cardiac cell types, but complete differentiation into functional cells has not yet been achieved. Previous methods of differentiation were based on pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 56 publications
(50 reference statements)
1
40
0
5
Order By: Relevance
“…anti-inflammatory and antifibrotic effects; stimulate endogenous repair by paracrine signaling (growth factors and microvesicles); 32,87,88 limited capacity for direct tissue replacement [78][79][80] stimulate endogenous repair by paracrine signaling (growth factors and microvesicles); limited capacity for direct tissue replacement 41,48,178 unclear; evidence for direct remuscularization 24,172 or no evidence of remuscularization; 112 evidence for paracrine effects 37,112,169 modulates gene expression Molecular Therapy Vol. 26 No 7 July 2018 1611 www.moleculartherapy.org Review of hematopoietic lineage CD markers (CD45, CD34, CD14, CD19, and HLA-DR); be plastic adherent when maintained under standard culture conditions; and exhibit the ability to form into colony-forming unit fibroblasts (CFU-Fs) and differentiate into osteoblasts, adipocytes, and chondroblasts in vitro.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…anti-inflammatory and antifibrotic effects; stimulate endogenous repair by paracrine signaling (growth factors and microvesicles); 32,87,88 limited capacity for direct tissue replacement [78][79][80] stimulate endogenous repair by paracrine signaling (growth factors and microvesicles); limited capacity for direct tissue replacement 41,48,178 unclear; evidence for direct remuscularization 24,172 or no evidence of remuscularization; 112 evidence for paracrine effects 37,112,169 modulates gene expression Molecular Therapy Vol. 26 No 7 July 2018 1611 www.moleculartherapy.org Review of hematopoietic lineage CD markers (CD45, CD34, CD14, CD19, and HLA-DR); be plastic adherent when maintained under standard culture conditions; and exhibit the ability to form into colony-forming unit fibroblasts (CFU-Fs) and differentiate into osteoblasts, adipocytes, and chondroblasts in vitro.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Under the proper conditions, MSCs are capable of transdifferentiating into functional cardiomyocytes in vivo and in vitro. [78][79][80] For example, transplantation of human MSCs, expressing a b-galactosidase reporter gene, into immunodeficient mice with experimental myocardial damage resulted in b-galactosidase + cardiomyocytes within the host myocardium, suggestive of cardiomyocyte differentiation of the xenografted MSCs. 81 Similarly, sex-mismatched cell therapy experiments, in porcine models of acute 32 and chronic MI, 82 provide evidence that engrafted male porcine MSCs differentiated into cardiomyocytes within the female host myocardium, as ascertained by co-localization of the Y chromosome with cardiac transcription factors GATA-4, Nkx2.5, and the structural cardiac protein a-sarcomeric actin.…”
Section: Msc Therapy: Mechanism Of Action In Cardiac Regenerationmentioning
confidence: 99%
“…In the present study, Sgsm3 KD ameliorated hypoxiainduced MSC death, which may be caused by Sgsm3 KD-induced increases in CX43. MI and subsequent ischemic processes under low oxygen conditions result in extensive cardiomyocyte loss, and MSC-based therapies are gaining attention as a way to replace current techniques [44]. Although complete differentiation into functional cells has not yet been achieved, MSCs can differentiate into cardiac cell types [10,44].…”
Section: Plos Onementioning
confidence: 99%
“…MI and subsequent ischemic processes under low oxygen conditions result in extensive cardiomyocyte loss, and MSC-based therapies are gaining attention as a way to replace current techniques [44]. Although complete differentiation into functional cells has not yet been achieved, MSCs can differentiate into cardiac cell types [10,44]. In vivo studies have demonstrated that MSC-derived differentiated cells have electrophysiological functions similar to cells originating from cardiac tissue [45,46].…”
Section: Plos Onementioning
confidence: 99%
“…La principal proteína de unión gap de comunicación eléctrica y bioquímica cardíaca es la conexina 43 (Cx43), además de estar presentes miosina de cadena pesada, alfa-actina y desmina (proteínas características de músculo estriado y músculo liso) [38].…”
Section: Inmunofenotipo Cardíacounclassified